Assessment of CO2 and NOx Emissions of One Diesel and One Bi-Fuel Gasoline/CNG Euro 6 Vehicles During Real-World Driving and Laboratory Testing - Dimaratos, Athanasios; Toumasatos, Zisimos; Doulgeris, Stylianos; Triantafyllopoulos, Georgios; Kontses, Anastasios; Samaras, Zissis (Frontiers in Mechanical Engineering, 2019)
The objective of this study is the assessment of the real-world environmental performance, and the comparison with laboratory measurements, of two Euro 6 passenger cars. The first is equipped with a common-rail diesel engine, Lean NOx Trap (LNT) and Diesel Particulate Filter (DPF), and the second is a bi-fuel gasoline/CNG (Compressed Natural Gas) one, equipped with Three Way Catalyst (TWC). The experimental campaign consisted of on-road and chassis dynamometer measurements. In the former test set, two driving routes were followed, one complying with the Real Driving Emissions (RDE) regulation, and another characterized by more dynamic driving. The aim of the latter route was to go beyond the regulatory limits and cover a wider range of real-world conditions and engine operating area. In the laboratory, the WLTC (Worldwide harmonized Light vehicles Test Cycle) was tested, applying the real-world road load of the vehicles. Both cars underwent the same tests, and these were repeated for the primary (CNG) and the secondary (gasoline) fuel of the bi-fuel vehicle. In all the tests, CO2 and NOx emissions were measured with a Portable Emissions Measurement System (PEMS). The results were analyzed on two levels, the aggregated and the instantaneous, in order to highlight the different emissions attributes under varying driving conditions. The application of the realistic road load in the WLTC limited its difference with the RDE compliant route, in terms of CO2 emissions. However, the aggressive driver behavior and the uphill roads of the Dynamic driving schedule resulted in around double CO2 emissions for both cars. The potential of natural gas to reduce CO2 emissions was also highlighted. Concerning the diesel car NOx emissions, the real-world results were significantly higher than the respective WLTC levels. On the other hand, the bi-fuel car exhibited very low NOx emissions with both fuels. Natural gas resulted in increased NOx emissions, compared to gasoline, always remaining below the Euro 6 limit, with only exception the Dynamic driving schedule. Finally, it was found that the overall cycle dynamics are not sufficient for the complete assessment of transient emissions and the instantaneous engine and aftertreatment behavior can reveal additional details.